# Class 9 RD Sharma Solutions – Chapter 5 Factorisation of Algebraic Expressions- Exercise 5.1

**Question 1: Factorize x**^{3} + x – 3x^{2} – 3

^{3}+ x – 3x

^{2}– 3

**Solution:**

x

^{3}+ x – 3x^{2}– 3Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the

Demo Class for First Step to Coding Course,specificallydesigned for students of class 8 to 12.The students will get to learn more about the world of programming in these

free classeswhich will definitely help them in making a wise career choice in the future.Here x is common factor in x

^{3}+ x and – 3 is common factor in – 3x^{2}– 3x

^{3}– 3x^{2}+ x – 3x

^{2}(x – 3) + 1(x – 3)Taking (x – 3) common

(x – 3) (x

^{2}+ 1)Therefore, x

^{3}+ x – 3x^{2}– 3 = (x – 3) (x^{2}+ 1)

**Question 2: Factorize a(a + b)**^{3} – 3a^{2}b(a + b)

^{3}– 3a

^{2}b(a + b)

**Solution:**

a(a + b)

^{3}– 3a^{2}b(a + b)Taking (a + b) as common factor

= a(a + b) {(a + b)

^{2}– 3ab}= a(a + b) {a

^{2}+ b^{2 }+ 2ab – 3ab}= a(a + b) (a

^{2}+ b^{2}– ab)

**Question 3: Factorize x(x**^{3} – y^{3}**) + 3xy(x – y)**

^{3}– y

**Solution:**

x(x

^{3}– y^{3}) + 3xy(x – y)= x(x – y) (x

^{2}+ xy + y^{2}) + 3xy(x – y)Taking x(x – y) as a common factor

= x(x – y) (x

^{2}+ xy + y^{2}+ 3y)= x(x – y) (x

^{2}+ xy + y^{2}+ 3y)

**Question 4: Factorize a ^{2}x^{2} + (ax^{2} + 1)x + a**

**Solution:**

a

^{2}x^{2}+ (ax^{2}+ 1)x + a= a

^{2}x^{2}+ a + (ax^{2}+ 1)x= a(ax

^{2}+ 1) + x(ax^{2}+ 1)= (ax

^{2}+ 1) (a + x)

**Question 5: Factorize x**^{2}** + y – xy – x**

**Solution:**

x

^{2}+ y – xy – x= x

^{2}– x – xy + y= x(x – 1) – y(x – 1)

= (x – 1) (x – y)

**Question 6: Factorize x ^{3} – 2x2y + 3xy**

^{2}

**– 6y**

^{3}**Solution:**

x

^{3}– 2x2y + 3xy^{2}– 6y^{3}= x

^{2}(x – 2y) + 3y^{2}(x – 2y)= (x – 2y) (x

^{2}+ 3y^{2})

**Question 7: Factorize 6ab – b**^{2}** + 12ac – 2bc**

**Solution:**

6ab – b

^{2}+ 12ac – 2bc= 6ab + 12ac – b

^{2}– 2bcTaking 6a common from first two terms and –b from last two terms

= 6a(b + 2c) – b(b + 2c)

Taking (b + 2c) common factor

**Question 8: Factorize (x**^{2}** + 1/x**^{2}**) – 4(x + 1/x) + 6**

**Solution:**

(x

^{2}+ 1/x^{2}) – 4(x + 1/x) + 6= x

^{2}+ 1/x^{2 }– 4x – 4/x + 4 + 2= x

^{2}+ 1/x^{2}+ 4 + 2 – 4/x – 4x= (x

^{2}) + (1/x)^{2}+ (-2)^{2}+ 2x(1/x) + 2(1/x)(-2) + 2(-2)xAs we know, x

^{2}+ y^{2}+ z^{2}+ 2xy + 2yz + 2zx = (x + y + z)^{2}So, we can write;

= (x + 1/x + (-2))

^{2}or (x + 1/x – 2)

^{2}Therefore, x

^{2}+ 1/x^{2}) – 4(x + 1/x) + 6 = (x + 1/x – 2)^{2}

**Question 9: Factorize x(x – 2) (x – 4) + 4x – 8**

**Solution:**

x(x – 2) (x – 4) + 4x – 8

= x(x – 2) (x – 4) + 4(x – 2)

= (x – 2) [x(x – 4) + 4]

= (x – 2) (x

^{2}– 4x + 4)= (x – 2) [x

^{2}– 2 (x)(2) + (2)^{2}]= (x – 2) (x – 2)

^{2}= (x – 2)

^{3}

**Question 10: Factorize (x + 2) (x**^{2}** + 25) – 10x**^{2}** – 20x**

**Solution:**

(x + 2) (x

^{2}+ 25) – 10x(x + 2)Take (x + 2) as common factor;

= (x + 2)(x

^{2}+ 25 – 10x)= (x + 2) (x

^{2}– 10x + 25)Expanding the middle term of (x

^{2}– 10x + 25)= (x + 2) (x

^{2}– 5x – 5x + 25)= (x + 2){x (x – 5) – 5 (x – 5)}

= (x + 2)(x – 5)(x – 5)

= (x + 2)(x – 5)

^{2}Therefore, (x + 2) (x

^{2}+ 25) – 10x (x + 2) = (x + 2)(x – 5)^{2}

**Question 11: Factorize 2a**^{2}** + 2√6 ab + 3b**^{2}

**Solution:**

2a

^{2}+ 2√6 ab + 3b^{2}Above expression can be written as (√2a)

^{2}+ 2 × √2a × √3b + (√3b)^{2}As we know, (p + q)

^{2}= p^{2}+ q^{2}+ 2pqHere p = √2a and q = √3b

= (√2a + √3b)

^{2}Therefore, 2a

^{2}+ 2√6 ab + 3b^{2}= (√2a + √3b)^{2}

**Question 12: Factorize (a – b + c)**^{2}** + (b – c + a)**^{2}** + 2(a – b + c) (b – c + a)**

**Solution:**

(a – b + c)

^{2}+ (b – c + a)^{2}+ 2(a – b + c) (b – c + a){Because p

^{2}+ q^{2}+ 2pq = (p + q)^{2}}Here p = a – b + c and q = b – c + a

= [a – b + c + b – c + a]

^{2}= (2a)

^{2}= 4a

^{2}

**Question 13: Factorize a**^{2}** + b**^{2}** + 2(ab + bc + ca)**

**Solution:**

a

^{2}+ b^{2}+ 2ab + 2bc + 2caAs we know, p

^{2 }+ q^{2}+ 2pq = (p + q)^{2}We get,

= (a + b)

^{2}+ 2bc + 2ca= (a + b)

^{2}+ 2c(b + a)Or (a + b)

^{2}+ 2c(a + b)Take (a + b) as common factor;

= (a + b)(a + b + 2c)

Therefore, a

^{2}+ b^{2}+ 2ab + 2bc + 2ca = (a + b)(a + b + 2c)

**Question 14: Factorize 4(x – y)**^{2}** – 12(x – y)(x + y) + 9(x + y)**^{2}

**Solution:**

Consider (x – y) = p, (x + y) = q

= 4p

^{2}– 12pq + 9q^{2}Expanding the middle term, -12 = -6 -6 also 4 × 9 = -6 × -6

= 4p

^{2}– 6pq – 6pq + 9q^{2}= 2p(2p – 3q) – 3q(2p – 3q)

= (2p – 3q) (2p – 3q)

= (2p – 3q)

^{2}Substituting back p = x – y and q = x + y;

= [2(x – y) – 3(x + y)]

^{2}= [2x – 2y – 3x – 3y ]^{2}= (2x – 3x – 2y – 3y)

^{2}= [-x – 5y]

^{2}= [(-1)(x + 5y)]

^{2}= (x + 5y)

^{2}Therefore, 4(x – y)

^{2}– 12(x – y)(x + y) + 9(x + y)^{2}= (x + 5y)^{2}

**Question 15: Factorize a**^{2}** – b**^{2}** + 2bc – c**^{2}

**Solution :**

a

^{2}– b^{2}+ 2bc – c^{2}As we know, (a – b)

^{2}= a^{2}+ b^{2}– 2ab= a

^{2}– (b – c)^{2}Also, we know, a

^{2}– b^{2}= (a + b)(a – b)= (a + b – c)(a – (b – c))

= (a + b – c)(a – b + c)

Therefore, a

^{2}– b^{2}+ 2bc – c^{2}=(a + b – c)(a – b + c)

**Question 16: Factorize a**^{2 }**+ 2ab + b**^{2}** – c**^{2}

**Solution:**

a

^{2}+ 2ab + b^{2}– c^{2}= (a

^{2}+ 2ab + b^{2}) – c^{2}= (a + b)

^{2}– (c)^{2}We know, a

^{2}– b^{2}= (a + b) (a – b)= (a + b + c) (a + b – c)

Therefore, a

^{2}+ 2ab + b^{2}– c^{2}= (a + b + c) (a + b – c)